2018
DOI: 10.3390/pr6020018
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal Pump Monitoring and Determination of Pump Characteristic Curves Using Experimental and Analytical Solutions

Abstract: Centrifugal pumps are widely used in the industry, especially in the oil and gas sector for fluids transport. Classically, these are designed to transfer single phase fluids (e.g., water) at high flow rates and relatively low pressures when compared with other pump types. As part of their constructive feature, centrifugal pumps rely on seals to prevent air entrapment into the rotor during its normal operation. Although this is a constructive feature, water should pass through the pump inlet even when the inlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The best pump efficiency (Q bep ) was 3.02 x 10 -3 m 3 /s. The influence of gas-water two-phase mixing on the characteristic curve of centrifugal pump was discussed in [8], the inoperability of pump vibration at different flow rates under these conditions is considered. The ability to use experimental research results for numerical modeling for design and training, as well as the ability to use vibration and sound analysis to capture changes in equipment operating conditions.…”
Section: An Experimental Study On Centrifugal Pump To Determine the Effect Of Radial Clearance On Pressure Pulsations Vibrations And Noismentioning
confidence: 99%
“…The best pump efficiency (Q bep ) was 3.02 x 10 -3 m 3 /s. The influence of gas-water two-phase mixing on the characteristic curve of centrifugal pump was discussed in [8], the inoperability of pump vibration at different flow rates under these conditions is considered. The ability to use experimental research results for numerical modeling for design and training, as well as the ability to use vibration and sound analysis to capture changes in equipment operating conditions.…”
Section: An Experimental Study On Centrifugal Pump To Determine the Effect Of Radial Clearance On Pressure Pulsations Vibrations And Noismentioning
confidence: 99%
“…This is primarily due to the absorption losses of short CdS wavelength and an interlinking individually or simultaneously; in case of interconnected parameters such as the motor's electrical signals and fluid pressure and temperature signals. In the latter case, synchronized measurements of different DOI : 10.36909/jer.EMSME.13881 parameters are performed and analyzed simultaneously to identify the fault and determine its root cause Stan et al, 2018). While these signals aid in fault diagnosis, they are still an indirect signature of the actual fault condition.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the geometric parameters of a centrifugal pump impeller results state that their modifications can have a significant impact [5] on its performance. Investigations show that the introduction of air into the water changes [6][7][8] the pump characteristic curve. Experiences with incorporating the testing of small water pumps in an engineering technology curriculum have shown that it is a versatile and economical tool for learning valuable techniques [9] in experimental testing.…”
Section: Introductionmentioning
confidence: 99%